Intensive care unit-acquired dysphagia – change in feeding route after a standardized dysphagia assessment in neurocritical care patients - Sarah Christina Reitz; Joanna Marly; Vanessa Neef; Jürgen Konczalla; Marcus Czabanka; Christian Grefkes-Hermann; Christian Foerch; Sriramya Lapa (Scientific Reports)
Abstract Background: Dysphagia is a frequent finding on intensive care units (ICUs) and is associated with increased reintubation rates, pneumonia, and prolonged ICU-stay. Only a limited numbers of ICUs have access to a Speech and Language Pathologist (SLP). Hence, it falls upon the critical care team to estimate dysphagia risk and define the safest feeding route. Therefore, the aim of this study was to evaluate if the feeding route established by the ICU-team is changed after a standardized dysphagia assessment (DA) by an SLP. Furthermore, we tried to identify predictors for the need of a SLP assessment looking at the change in feeding route (CIFR) after DA. Methods: We performed a retrospective analysis of patients consecutively admitted for at least 48 h in 2018, to the ICU of the Department of Neurology and Neurosurgery. Following variables were assessed: Referral to an SLP, feeding route before and after DA by an SLP, main diagnosis, and ventilation parameters. Results: From 497 included patients (65 years, IQR 51–77), 148 received a DA, confirming dysphagia in 125 subjects. DA by the SLP resulted in a significant CIFR, with 32 (21.6%) subjects receiving stricter diets, and in 29 (19.6%) cases a reduction of dietary recommendations. 50 patients lacked readiness for oral intake due to severely affected oral phase or reduced consciousness. Conclusion: Dysphagia is a frequent finding in the Neuro-ICU. Assessment of dysphagia-risk and safest feeding route differ significantly between the SLP and the critical care team. Besides implementation of standardized operating procedures for DA, the presence of ICU-specific trained SLP should be mandatory.